Assessment of community-acquired urinary tract infections treatment in the emergency department: a retrospective study - Ghaleb, Marie Ange; Zoghbi, Antoine; Bou Chebl, Zeina; Lilly, Eddy; Saliba, Gebrayel; Choucair, Jacques; Ibrahim, Racha (Frontiers in Cellular and Infection Microbiology, 2024)
IntroductionUrinary tract infection (UTI) is one of the most common medical complaints in the emergency department (ED). The aim of this study was to assess the real indication of an initial broad-spectrum treatment administered in the ED for hospitalized patients with a diagnosis of community-acquired UTI (CAUTI).Materials and methodsThis is a monocentric observational retrospective study conducted in the ED of one of the largest tertiary care centers in Lebanon, on a two-year period, including adult patients admitted to the hospital for a CAUTI. The primary outcome was to evaluate the need of downgrading empirical antibiotherapy started in the ED. Secondary outcomes included a description of CAUTIs characteristics: prevalence and risk factors for (extended spectrum beta lactamases) ESBL-related infection, complicated and uncomplicated UTIs, empirical and targeted treatment, and finally the rate of adherence to local guidelines.ResultsThe most isolated strains on urine cultures were gram negative bacilli (GNB) with 29.1% producing ESBL; 69.4% of patients received an ESBL-targeting empirical treatment in the ED, in agreement with local guidelines, 46% of which needed a downgrade. Amikacin adjunction was only indicated in 42.8% of the cases. Patients who received antibiotics in the last 6 months had a 2.36 times higher risk of developing an ESBL-related infection.ConclusionThis study showed a high adherence rate to local recommendations suggesting the use of empirical ESBL-targeting antibiotherapy even in uncomplicated UTIs. However, the frequent need of de-escalation highlights the importance of establishing an efficient multi-drug resistant (MDR) bacteria surveillance system in the community in order to elaborate a stewardship program with more solid local guidelines.